ADVENTURE TOURISM: STRATEGI PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT DI DESA SAMBANGAN, KABUPATEN BULELENG, BALI - Adistiyani Laras Hati; Wirawan, Putu Eka; I Wayan Kiki Sanjaya (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
Along with the massive development of tourism, this has led to the emergence of the development of several tourism alternatives, such as: tourist villages and ecotourism which have become alternatives to the development of mass tourism. Sambangan Village has several charming tourist attractions that are no less beautiful than other tourist areas. The aim of this research is to find potentials, supporting and inhibiting factors and find out strategies for developing community-based adventure tourism in Sambangan Village, Buleleng Regency, Bali. This research uses a qualitative approach which is a research method used to examine the condition of natural objects. The data collection techniques used in this research are observation and interviews. The data has been collected, processed and analyzed descriptively using the SWOT analysis tool. The results of the research show that based on the square of the SWOT matrix, it can be seen that the position of the Sambangan tourist village is currently in the growth quadrant I position (growth) with the quadrant position in its place in the IB quadrant position, which means that the strategic position of the Sambangan tourist village is in a stable growth strategy position. If the Sambangan tourist village is in this position, the competitive power possessed by the Sambangan tourist village is relatively small compared to the opportunities available. In fact, the Sambangan tourist village can only grow according to its own capabilities. In other words, the growth of the Sambangan tourist village is not drastic (fast), but gradual.